HydrologyCoCT - a regenerative prototype for the reintroduction of hydrology in the City of Cape Town - Barker, A.A.J. (Arthur Adrian Johnson) (University of Pretoria, 2013)
Dissertation (MArch(Prof))--University of Pretoria, 2011.